TREN GLAMOR PADA MASYARAKAT DI GAMPONG JEURAM KECAMATAN SEUNAGAN KABUPATEN NAGAN RAYA - Baihaki Baihaki; Afrizal Tjoetra; Irma Juraida (Jurnal Society : Pengamat Perubahan Sosial, 2022)
In modern times, glamor is a trend that is followed or fulfilled by everyone, not only followed by people who live in urban areas but people who live in rural areas, so that the behavior and social changes in these communities can be categorized as problems in people’s lives in essence because it has deviated from previous life norms. This study aims to determine public opinion about the existing glamorous trends in the Jeuram village community in the district of Nagan Raya. District and can be used as a reference if an improvement is made from the impact of the glamorous trend. In this study, researchers used the theory of self-concept that was sparked by bay James B. Harlock the method used in this study is a qualitative method with the determination of informants by purposive sampling. The results showed that the glamor trend in the people of Jeuram village, Seunagan sub-district, Nagan Raya district had factors such as environment, economy, social media, and competition. While the forms include fashion, household appliances, and communication.